Authenticity in Transition: Changing Practices in Contemporary Art Making and Conservation - García Fernández-Villa, Silvia (Ge-conservacion, 2016)
Authenticity in Transition: Changing Practices in Contemporary Art Making and Conservation Erma Hermens, Frances Robertson (eds) (2016) Archetype Publications Páginas: 205 ISBN: 9781909492363